The nicotinic cholinergic system function in the human brain. (September 2015) - Nees, Frauke
Abstract: Research on the nicotinic cholinergic system function in the brain was previously mainly derived from animal studies, yet, research in humans is growing. Up to date, findings allow significant advances on the understanding of nicotinic cholinergic effects on human cognition, emotion and behavior using a range of functional brain imaging approaches such as pharmacological functional magnetic resonance imaging or positron emission tomography. Studies provided insights across various mechanistic psychological domains using different tasks as well as at rest in both healthy individuals and patient populations, with so far partly mixed results reporting both enhancements and decrements of neural activity related to the nicotinic cholinergic system. Moreover, studies on the relation between brain structure and the nicotinic cholinergic system add important information in this context. The present review summarizes the current status of human brain imaging studies and presents the findings within a theoretical and clinical perspective as they may be useful not only for an advancement of the understanding of basic nicotinic cholinergic-related mechanisms, but also for the development and integration of psychological and pharmacological treatment approaches. Patterns of functional neuroanatomy and neural circuitry across various cognitive and emotional domains may be used as neuropsychological markers of mental disorders such as addiction, Alzheimer's disease, Parkinson disease or schizophrenia, where nicotinic cholinergic system changes are characteristic. This article is part of the Special Issue entitled 'The Nicotinic Acetylcholine Receptor: From Molecular Biology to Cognition'. Highlights: The nicotinic cholinergic system modulates a large set of human brain regions. The nicotinic cholinergic system induces neuronal activation–deactivation patterns. The nicotinic cholinergic system affects gray and white matter tracts. The nicotinic cholinergic system confers neuronal effects on psychological domains.